A 2.3/3.3 GHz Dual Band Antenna Design for WiMax Applications - Adit Kurniawan; Iskandar Iskandar; P.H. Mukti (LPPM ITB, 2010)
A triangular-slot antenna with rectangular patch for 2.3/3.3 GHz WiMax applications has been implemented on DICLAD 527 substrate (relative permittivity Îµr = 2.5) with 1.524 mm of substrate thickness. A rectangular patch printed on one side of the substrate is fed by a 50 â„¦ microstrip line and acts as the frequency tuning stub, while the triangular slot is positioned on the opposite side of the substrate, center lined to the rectangular stub. From the measurement results based on VSWR = 2 or equal to the return loss of 9.53 dB, at the lower band of 2.3 GHz the resulting impedance bandwidth is 290 MHz (from 2.16 to 2.45 GHZ) and at the upper band of 3.3 GHz is 370 MHz (from 3.31 to 3.68GHz), providing services for 2.3 GHz and 3.3 GHz frequency bands allocated for WiMax applications. The antenna gain measurement at 2.3 GHz frequency band is almost agrees with the simulation result of 3.2 dBi. While at 3.3 GHz the gain is approximately 4.4 dBi and continues to decrease with increasing frequency. The antenna gain measurement achieves maximum of 4.8 dBi (6 dBi from simulation) at about 3 GHz. The simulation and measurement results are evaluated and discussed.